2018
DOI: 10.1177/0146167217744196
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Reflection as a Moderator of Attitude Strength Versus Attitude Bolstering: Implications for Attitude Similarity and Attraction

Abstract: "Strong" attitudes often have greater impact than "weak" attitudes. However, emerging research suggests that weak (uncertain) attitudes can substantially influence thinking or behavior. We propose metacognitive reflection as a moderator between traditional strength patterns and these emerging attitude bolstering patterns. Across six studies, research participants encountered a target person who agreed or disagreed with participants' attitudes. When focused on evaluating the target, attitudes predicted target e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
5
25
0
1
Order By: Relevance
“…We also examined whether we replicated previous findings that the antecedents to attitude strength moderated the attitude similarity-affective attraction effect (Montoya and Horton, 2013;Sawicki and Wegener, 2018). Consistent with previous work, we found evidence for an attitude-by-strength-related properties interaction (see Figure 3), r = 0.13, p = 0.01, 95% CI: [0.04, 0.23].…”
Section: Moderation Of the Attitude Similarity-attraction Effectsupporting
confidence: 87%
See 1 more Smart Citation
“…We also examined whether we replicated previous findings that the antecedents to attitude strength moderated the attitude similarity-affective attraction effect (Montoya and Horton, 2013;Sawicki and Wegener, 2018). Consistent with previous work, we found evidence for an attitude-by-strength-related properties interaction (see Figure 3), r = 0.13, p = 0.01, 95% CI: [0.04, 0.23].…”
Section: Moderation Of the Attitude Similarity-attraction Effectsupporting
confidence: 87%
“…For example, when attitudes are based on equally high levels of knowledge, similarity with relatively univalent (rather than ambivalent) attitudes better predict liking and desire to talk with an attitudinally similar other (see Wallace et al, 2020). Similarly, when perceivers focus on forming an impression of a target, similarity of attitudes held with confidence vs. doubt better predict affective attraction (Sawicki and Wegener, 2018). A recent meta-analysis found that attitudes more central or important (vs. peripheral or unimportant) to participants' identities produced larger similarity-attraction effect sizes (Montoya and Horton, 2013).…”
Section: Antecedents To Attitude Strengthmentioning
confidence: 99%
“…consider metacognitive properties of the attitude), they become more attracted to someone with whom they agree if they are relatively uncertain about their own attitude (Sawicki & Wegener, 2018). Although past research had independently shown that features like uncertainty could undermine or increase an attitude's influence, Sawicki and Wegener (2018) identify metacognitive reflection as the key moderator of uncertainty's effects on attitudinal outcomes. This theoretical distinction presents a set of guiding principles to help researchers predict when traditional strength patterns would emerge (i.e.…”
Section: Bolstering Versus Strength Motivationsmentioning
confidence: 99%
“…However, if certainty reflects an attitude's strength, confidently held attitudes should better guide a person's evaluation of someone else with whom they agree or disagree. Indeed, this is the case when people are merely focused on evaluating a target (Sawicki & Wegener, 2018). However, affiliating with attitudinally similar others can be an alluring opportunity to bolster one's own attitude (e.g.…”
Section: Bolstering Versus Strength Motivationsmentioning
confidence: 99%
See 1 more Smart Citation